Industrial automation : circuit design and components - Pessen, David W. ([S.l.] : Wiley-Interscience, 1989)
The first book to combine all of the various topics relevant to low-cost automation. Practical approach covers methods immediately applicable to industrial problems, showing how to select the most appropriate control method for a given application, then design the necessary circuit. Focuses on the control circuits and devices (electronic, electro-mechanical, or pneumatic) used in small- to mid-size systems. Stress is on on-off (binary) control as opposed to continuous feedback (analog) control. Discusses well-known procedures and their modifications, and a number of original techniques and circuit design methods. Covers ``flexible automation,'' including the use of microcomputers.